Distribution of health problems at the general outpatients' clinic of the University of Hong Kong-Shenzhen Hospital: A cross-sectional study - Kai Chen; Zhuo Li; Ruihong Liu; Yanyan Zhu; Weihui Yan; Ng Amy Pui Pui; Zhiyuan Chen (Frontiers Media S.A., 2022)
ObjectiveThe study aimed to understand the distribution of health problems of a general practice clinic to provide guidance on how to develop primary care in Shenzhen, China.Study designThis is a cross-sectional study.MethodsPatients' sociodemographic data and diagnoses were recorded from the electronic medical record system of the University of Hong Kong-Shenzhen Hospital from Jan 2014 to Dec 2020 and coded using the International Classification of Primary Care-2. Descriptive statistics were used to describe the distribution of health problems.ResultsA total of 368,167 health problems were recorded. Respiratory, digestive, musculoskeletal, general, and cardiovascular were the top five categories, which accounted for 67.71% of the total in this study. Acute upper respiratory tract infection (AURTI) was the most common health problem (6.67%). Chronic diseases, including hypertension and diabetes mellitus, accounted for about 7% of all health problems. The proportion of cardiovascular problems increased significantly with age (r = 0.96, P < 0.05). The proportion of consultations for mental health problems was low in all age groups.ConclusionsThe results represent an understanding of the common health problems of patients in Shenzhen city, which can provide a reference for preventing diseases and developing primary care.